Surface modification treatment method for improving surface hardness of magnesium alloy
By using a mixed powder of cobalt-based tungsten carbide powder and aluminum powder on the surface of the magnesium alloy for discharge plasma sintering, a metallurgical-combined hard coating was formed, which solved the problem of insufficient surface hardness of the magnesium alloy and achieved the surface hardness of the magnesium alloy. Significant improvement.
Patent Information
- Application Number
- CN202411575007.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to effectively improve the surface hardness of magnesium alloys, resulting in limitations in its application in scenarios of contact and friction with the outside of the mechanical structure and environment.
By using a mixed powder of cobalt-based tungsten carbide powder and aluminum powder as the hard coating material, discharge plasma sintering treatment is used to melt the aluminum powder and form a metallurgical bond with the magnesium alloy matrix to form a machinery of aluminum and cobalt-based carbides. The mixture is a hard coating with the main components.
The surface hardness of magnesium alloy is significantly improved, the bonding force between cobalt-based tungsten carbide and magnesium alloy matrix is enhanced, and the firmness and stability of the coating are ensured.
Smart Images

Figure CN119426591A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnesium alloy preparation, and in particular to a surface modification method for improving the surface hardness of a magnesium alloy. Background Art
[0002] As the lightest metal structural material, magnesium alloy has a lower density, which is of great significance to the country's future energy conservation and emission reduction. Its advantages of high specific strength and specific stiffness make it widely used in transportation, aerospace, portable equipment and other fields.
[0003] Due to the low hardness of magnesium alloy, its application is limited in scenarios where mechanical structures are in contact and friction with the outside of the environment, especially in the moving connection parts of mechanical structures and the outside and the environment, such as the joints of robot arms and the parts of the car body that often come into contact with cargo.
[0004] In order to solve the above technical problems, existing methods have proposed methods such as surface micro-arc oxidation technology and ion sputtering equipment high hardness titanium aluminum nitride film process, which improve the surface hardness of the magnesium alloy by modifying the surface of the magnesium alloy. However, although the above-mentioned surface micro-arc oxidation technology can form a ceramic layer on the surface of the magnesium alloy, thereby improving the hardness and wear resistance of the surface of the magnesium alloy to a certain extent, the ceramic layer formed by this method is brittle and easily peeled off from the surface of the magnesium alloy, making it difficult to effectively improve the surface hardness of the magnesium alloy. Although the above-mentioned ion sputtering equipment high hardness titanium nitride / aluminum film process can also improve the surface hardness, the thickness of the film layer formed is relatively small, usually several microns thick, resulting in the surface film layer being easily broken and peeled off when the magnesium alloy encounters impact, and it is also difficult to effectively improve the surface hardness of the magnesium alloy.
[0005] In summary, the above methods are difficult to effectively improve the surface hardness of magnesium alloys, resulting in limitations in the application of magnesium alloys in scenarios of external contact and friction between mechanical structures and the environment. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a surface modification method for improving the surface hardness of magnesium alloy. The present invention uses a mixed powder of cobalt-based tungsten carbide powder and aluminum powder as a hard coating material for the surface of the magnesium alloy substrate, and uses spark plasma sintering to melt the aluminum powder. The aluminum powder can not only wrap the cobalt-based tungsten carbide powder during volume expansion and flow during the melting process, but also can form a metallurgical bond with the magnesium alloy substrate after melting, thereby forming a hard coating with a mechanical mixture of aluminum and cobalt-based carbide as the main component on the surface of the magnesium alloy, so that the cobalt-based tungsten carbide can be firmly and stably anchored on the surface of the magnesium alloy substrate, greatly improving the bonding force between the cobalt-based tungsten carbide and the magnesium alloy substrate, thereby effectively improving the surface hardness of the magnesium alloy substrate.
[0007] A surface modification method for improving the surface hardness of a magnesium alloy according to the present invention is achieved by the following technical scheme:
[0008] The present invention provides a surface modification method for improving the surface hardness of a magnesium alloy, comprising the following steps:
[0009] Step 1, preprocessing:
[0010] The magnesium alloy substrate to be treated is pretreated to remove surface impurities and oxide layer to obtain a clean magnesium alloy substrate.
[0011] It should be noted that the present invention takes into account the possible presence of grease and an oxide layer on the surface of the magnesium alloy substrate to be treated, which will affect the composite effect of the coating and the substrate. Therefore, the surface of the magnesium alloy needs to be pretreated before forming the coating to remove surface impurities and the oxide layer, so as to help improve the interface bonding strength of the base film.
[0012] Step 2, mix cobalt-based tungsten carbide powder and aluminum powder:
[0013] The cobalt-based tungsten carbide powder and the aluminum powder are mixed to obtain a hard coating material.
[0014] It should be noted that the hardness of cobalt-based tungsten carbide powder is close to that of diamond, and it is a good conductor of electricity and heat. In addition, the melting point of cobalt-based tungsten carbide powder is 3422°C, the boiling point is 6000°C, and the chemical properties are stable. Therefore, the present invention uses cobalt-based tungsten carbide powder as the main raw material for forming a hard coating. However, the present invention takes into account the high melting point of cobalt-based tungsten carbide powder, and its sintering temperature is much higher than the melting point and boiling point of magnesium alloy, that is, if the cobalt-based tungsten carbide is heated to sinter, the matrix magnesium alloy will be completely evaporated. At the same time, considering that cobalt-based tungsten carbide is relatively brittle, aluminum powder is added to the cobalt-based tungsten carbide powder. Since the melting point of aluminum powder is close to that of magnesium alloy, and aluminum atoms and magnesium atoms can form an aluminum-magnesium phase, it is beneficial to the combination of the matrix and the hard coating. At the same time, the volume expansion and flow of aluminum powder during the melting process can wrap up the cobalt-based tungsten carbide powder, and after cooling and solidification, aluminum and the matrix magnesium alloy are metallurgically bonded. The aluminum powder also wraps the hard point - cobalt-based tungsten carbide. Therefore, the present invention uses the mixed powder formed by cobalt-based tungsten carbide powder and aluminum powder as the hard coating material, so that the hard coating material used has excellent comprehensive performance.
[0015] Step 3, spark plasma sintering treatment:
[0016] The hard coating material is evenly spread on the surface of the clean magnesium alloy substrate to obtain a premix; the premix is subjected to a spark plasma sintering treatment to increase the surface hardness of the magnesium alloy substrate to obtain a coating composite material.
[0017] It should be noted that, considering the fact that the hard coating material is in powder form, has a large specific surface area, and is easily oxidized, the present invention preferably uses a spark plasma sintering process to compound the hard coating material and the magnesium alloy substrate. In addition, during the spark plasma sintering process, the hard coating material is laid on the surface of the magnesium alloy substrate, so that the hard coating material part is subjected to high pressure and discharge heating, wherein the low-melting-point aluminum powder melts, forms a metallurgical bond with the magnesium alloy substrate, and infiltrates, disperses and wraps the cobalt-based tungsten carbide powder, thereby forming a hard coating with a mechanical mixture of aluminum and cobalt-based carbide as the main component on the surface of the magnesium alloy. In addition, in the mechanical mixture of the hard coating formed by the present invention, the cobalt-based tungsten carbide acts as a hard point, and the aluminum inclusion frame acts to connect the magnesium alloy substrate and disperse the cobalt-based tungsten carbide, so that the cobalt-based tungsten carbide can be firmly and stably anchored on the surface of the magnesium alloy substrate, greatly improving the bonding force between the cobalt-based tungsten carbide and the magnesium alloy substrate, thereby effectively improving the surface hardness of the magnesium alloy substrate.
[0018] In some preferred embodiments of the present invention, the volume ratio of the cobalt-based tungsten carbide powder to the aluminum powder is 1:1-5.
[0019] In some more preferred embodiments of the present invention, the volume ratio of the cobalt-based tungsten carbide powder to the aluminum powder is 1:1.
[0020] In some preferred embodiments of the present invention, the sintering pressure of the spark plasma sintering process is 0.8t-1t, and the sintering temperature is 400°C-500°C.
[0021] In some more preferred embodiments of the present invention, the sintering pressure of the spark plasma sintering process is 1t.
[0022] In some more preferred embodiments of the present invention, the sintering temperature of the spark plasma sintering process is 450°C.
[0023] In some preferred embodiments of the present invention, the holding time of the spark plasma sintering treatment is 1 min to 3 min.
[0024] In some preferred embodiments of the present invention, the amount of the hard coating material laid on the surface of the clean magnesium alloy substrate is 0.00187 g / mm 2 ~0.00597g / mm 2 .
[0025] In some preferred embodiments of the present invention, the average particle size of the cobalt-based tungsten carbide powder is 10 μm to 30 μm.
[0026] In some preferred embodiments of the present invention, the average particle size of the aluminum powder is 10 μm to 20 μm.
[0027] In some preferred embodiments of the present invention, the pretreatment includes ultrasonic cleaning and polishing performed in sequence, so as to remove impurities such as oil stains on the surface of the magnesium alloy substrate by ultrasonic cleaning, and then remove impurities such as oxide layers on the surface of the magnesium alloy substrate by polishing.
[0028] In some preferred embodiments of the present invention, the cleaning liquid for the ultrasonic cleaning treatment is water, and the ultrasonic time is 10 min to 20 min.
[0029] In some preferred embodiments of the present invention, the polishing process is performed by the following steps:
[0030] The composite surface of the magnesium alloy substrate after ultrasonic cleaning was polished with 400 mesh, 800 mesh and 1200 mesh fine sandpaper in sequence until the surface completely exposed the metallic luster, which was considered to be completely removed the oxide scale.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The present invention first removes impurities and oxide layers on the surface of the magnesium alloy substrate to be treated by pretreatment, so as to improve the interfacial bonding strength of the base film. Then, a mixed powder of cobalt-based tungsten carbide powder and aluminum powder is used as a hard coating material, which is laid on the surface of the pretreated magnesium alloy substrate, and treated by spark plasma sintering, so that the cobalt-based tungsten carbide powder and the aluminum powder are treated by spark plasma sintering, and the aluminum powder expands and flows in the melting process to wrap the cobalt-based tungsten carbide powder, and the aluminum powder can form a metallurgical bond with the magnesium alloy substrate after melting, so as to form a hard coating with a mechanical mixture of aluminum and cobalt-based carbide as the main component on the surface of the magnesium alloy, so that the cobalt-based tungsten carbide can be firmly and stably anchored on the surface of the magnesium alloy substrate, greatly improving the bonding strength between the cobalt-based tungsten carbide and the magnesium alloy substrate, thereby effectively improving the surface hardness of the magnesium alloy substrate.
[0033] The preparation method of the present invention has simple procedures, short preparation time and high preparation efficiency; and the formed hard coating has strong bonding force with the surface of the magnesium alloy, and can significantly improve the surface hardness of the magnesium alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is the average particle size distribution diagram of the aluminum powder used in the present invention.
[0035] Figure 2 This is the average particle size distribution diagram of the cobalt-based tungsten carbide used in the present invention.
[0036] Figure 3 This is a photograph of the original AZ31 magnesium alloy plate of Comparative Example 3.
[0037] Figure 4 This is a photograph of the 1 mm graphite paper used in the present invention.
[0038] Figure 5 This is the process curve of the spark plasma sintering treatment of Example 8.
[0039] Figure 6 is a photograph of the coating composite material of Example 1.
[0040] Figure 7 is a photograph of the coating composite material of Example 2.
[0041] Figure 8 This is a photograph of the coating composite material of Example 3.
[0042] Fig. 9 This is a photograph of the coating composite material of Example 4.
[0043] Fig.10 This is a photograph of the coating composite material of Example 5.
[0044] Fig.11 is a photograph of the coating composite material of Example 6.
[0045] Fig.12 is a photograph of the coating composite material of Example 7.
[0046] Fig.13 This is a photograph of the coating composite material of Comparative Example 1.
[0047] Fig.14 This is a photograph of the coating composite material of Comparative Example 2. DETAILED DESCRIPTION
[0048] The technical solutions in the embodiments of the present invention will be described clearly and completely below. It should be noted that the particle size distribution of the aluminum powder used in the following embodiments of the present invention is as follows: Figure 1 As shown in Figure 2, the average particle size of aluminum powder is distributed in the range of 10 μm to 20 μm, and the density of aluminum powder is 2.70 g / cm 3 The particle size distribution of the cobalt-based tungsten carbide powder used is as follows: Figure 2 As shown in the figure, the average particle size of cobalt-based tungsten carbide is distributed in the range of 10 μm to 30 μm, and the density of cobalt-based tungsten carbide powder is 16.24 g / cm 3 ; and the magnesium alloy substrate to be treated used in the following embodiments of the present invention is AZ31 magnesium alloy.
[0049] Example 1
[0050] This embodiment provides a surface modification method for improving the surface hardness of a magnesium alloy, comprising the following steps:
[0051] Step 1, preprocessing:
[0052] 1.1) Use an electric spark cutting machine to cut the magnesium alloy substrate to be processed into Figure 3 As shown, the magnesium alloy sample has a diameter of 40 mm and a thickness of 2 mm.
[0053] 1.2) Add an appropriate amount of clean water into the ultrasonic cleaning machine, put the cut magnesium alloy sample into the machine, turn on the ultrasonic cleaning machine, and perform cleaning for 15 minutes. After cleaning, use tweezers to take out the magnesium alloy sample and wipe it clean to obtain the magnesium alloy sample after ultrasonic cleaning.
[0054] 1.3) The composite surface of the magnesium alloy substrate after ultrasonic cleaning is polished with 400 mesh, 800 mesh and 1200 mesh fine sandpaper in sequence until the surface completely reveals the metallic luster, thereby obtaining a clean magnesium alloy substrate.
[0055] Step 2, mix cobalt-based tungsten carbide powder and aluminum powder:
[0056] According to the ratio of cobalt-based tungsten carbide powder to aluminum powder of 1:3 by volume, corresponding amounts of cobalt-based tungsten carbide powder and aluminum powder are weighed and mixed to obtain a hard coating material.
[0057] Step 3, spark plasma sintering treatment:
[0058] 3.1) Place a layer of graphite mold at the bottom. Figure 4 The graphite paper with a thickness of 1 mm is shown, and then the clean magnesium alloy substrate obtained in 1.3) is placed on the graphite paper, and then the hard coating material obtained in step 2 is coated at a temperature of 0.00224 g / mm 2 The amount of the coating material is evenly spread on the clean surface of the magnesium alloy substrate obtained in 1.3), and then three layers of graphite paper with a thickness of 1 mm are placed on the hard coating material to obtain a premix.
[0059] 3.2) The premix obtained in 3.1) was placed in a spark plasma sintering furnace, and the process parameters of the spark plasma sintering treatment were set as follows: sintering pressure of 1t, sintering temperature of 450°C, and pressure holding time of 2min.
[0060] 3.3) After the spark plasma sintering treatment is completed, the magnesium alloy substrate is cooled to room temperature, and a hard coating is formed on the surface of the magnesium alloy substrate to obtain a coating composite material.
[0061] Example 2
[0062] This embodiment provides a surface modification method for improving the surface hardness of a magnesium alloy, comprising the following steps:
[0063] Step 1, preprocessing:
[0064] 1.1) Use an electric spark cutting machine to cut the magnesium alloy substrate to be processed into Figure 3 As shown, the magnesium alloy sample has a diameter of 40 mm and a thickness of 2 mm.
[0065] 1.2) Add an appropriate amount of clean water into the ultrasonic cleaning machine, put the cut magnesium alloy sample into the machine, turn on the ultrasonic cleaning machine, and perform cleaning for 15 minutes. After cleaning, use tweezers to take out the magnesium alloy sample and wipe it clean to obtain the magnesium alloy sample after ultrasonic cleaning.
[0066] 1.3) The composite surface of the magnesium alloy substrate after ultrasonic cleaning is polished with 400 mesh, 800 mesh and 1200 mesh fine sandpaper in sequence until the surface completely reveals the metallic luster, thereby obtaining a clean magnesium alloy substrate.
[0067] Step 2, mix cobalt-based tungsten carbide powder and aluminum powder:
[0068] According to the ratio of cobalt-based tungsten carbide powder to aluminum powder of 1:3 by volume, corresponding amounts of cobalt-based tungsten carbide powder and aluminum powder are weighed and mixed to obtain a hard coating material.
[0069] Step 3, spark plasma sintering treatment:
[0070] 3.1) Place a layer of graphite mold at the bottom. Figure 4 The graphite paper with a thickness of 1 mm is shown, and then the clean magnesium alloy substrate obtained in 1.3) is placed on the graphite paper, and then the hard coating material obtained in step 2 is coated at a temperature of 0.00224 g / mm 2 The amount of the coating material is evenly laid on the clean magnesium alloy substrate surface obtained in 1.3), and then three layers of graphite paper with a thickness of 1 mm are placed on the hard coating material to obtain a premix.
[0071] 3.2) The premix obtained in 3.1) was placed in a spark plasma sintering furnace, and the process parameters of the spark plasma sintering treatment were set as follows: sintering pressure 1t, sintering temperature 500°C, and pressure holding time 2min.
[0072] 3.3) After the spark plasma sintering treatment is completed, the magnesium alloy substrate is cooled to room temperature, and a hard coating is formed on the surface of the magnesium alloy substrate to obtain a coating composite material.
[0073] That is, the difference between this embodiment and embodiment 1 is only that:
[0074] In this embodiment, the sintering temperature is 500°C.
[0075] Example 3
[0076] This embodiment provides a surface modification method for improving the surface hardness of a magnesium alloy, comprising the following steps:
[0077] Step 1, preprocessing:
[0078] 1.1) Use an electric spark cutting machine to cut the magnesium alloy substrate to be processed into Figure 3 As shown, the magnesium alloy sample has a diameter of 40 mm and a thickness of 2 mm.
[0079] 1.2) Add an appropriate amount of clean water into the ultrasonic cleaning machine, put the cut magnesium alloy sample into the machine, turn on the ultrasonic cleaning machine, and perform cleaning for 15 minutes. After cleaning, use tweezers to take out the magnesium alloy sample and wipe it clean to obtain the magnesium alloy sample after ultrasonic cleaning.
[0080] 1.3) The composite surface of the magnesium alloy substrate after ultrasonic cleaning is polished with 400 mesh, 800 mesh and 1200 mesh fine sandpaper in sequence until the surface completely reveals the metallic luster, thereby obtaining a clean magnesium alloy substrate.
[0081] Step 2, mix cobalt-based tungsten carbide powder and aluminum powder:
[0082] According to the ratio of cobalt-based tungsten carbide powder to aluminum powder of 1:3 by volume, corresponding amounts of cobalt-based tungsten carbide powder and aluminum powder are weighed and mixed to obtain a hard coating material.
[0083] Step 3, spark plasma sintering treatment:
[0084] 3.1) Place a layer of graphite mold at the bottom. Figure 4 The graphite paper with a thickness of 1 mm is shown, and then the clean magnesium alloy substrate obtained in 1.3) is placed on the graphite paper, and then the hard coating material obtained in step 2 is coated at a temperature of 0.00224 g / mm 2 The amount of the coating material is evenly spread on the clean surface of the magnesium alloy substrate obtained in 1.3), and then three layers of graphite paper with a thickness of 1 mm are placed on the hard coating material to obtain a premix.
[0085] 3.2) The premix obtained in 3.1) was placed in a spark plasma sintering furnace, and the process parameters of the spark plasma sintering treatment were set as follows: sintering pressure 1t, sintering temperature 400°C, and pressure holding time 2min.
[0086] 3.3) After the spark plasma sintering treatment is completed, the magnesium alloy substrate is cooled to room temperature, and a hard coating is formed on the surface of the magnesium alloy substrate to obtain a coating composite material.
[0087] That is, the difference between this embodiment and embodiment 1 is only that:
[0088] In this embodiment, the sintering temperature is 400°C.
[0089] Example 4
[0090] This embodiment provides a surface modification method for improving the surface hardness of a magnesium alloy, comprising the following steps:
[0091] Step 1, preprocessing:
[0092] 1.1) Use an electric spark cutting machine to cut the magnesium alloy substrate to be processed into Figure 3 As shown, the magnesium alloy sample has a diameter of 40 mm and a thickness of 2 mm.
[0093] 1.2) Add an appropriate amount of clean water into the ultrasonic cleaning machine, put the cut magnesium alloy sample into the machine, turn on the ultrasonic cleaning machine, and perform cleaning for 15 minutes. After cleaning, use tweezers to take out the magnesium alloy sample and wipe it clean to obtain the magnesium alloy sample after ultrasonic cleaning.
[0094] 1.3) The composite surface of the magnesium alloy substrate after ultrasonic cleaning is polished with 400 mesh, 800 mesh and 1200 mesh fine sandpaper in sequence until the surface completely reveals the metallic luster, thereby obtaining a clean magnesium alloy substrate.
[0095] Step 2, mix cobalt-based tungsten carbide powder and aluminum powder:
[0096] According to the ratio of cobalt-based tungsten carbide powder to aluminum powder of 1:1 by volume, corresponding amounts of cobalt-based tungsten carbide powder and aluminum powder are weighed and mixed to obtain a hard coating material.
[0097] Step 3, spark plasma sintering treatment:
[0098] 3.1) Place a layer of graphite mold at the bottom. Figure 4 The graphite paper with a thickness of 1 mm is shown, and then the clean magnesium alloy substrate obtained in 1.3) is placed on the graphite paper, and then the hard coating material obtained in step 2 is coated at a temperature of 0.00348 g / mm 2 The amount of the coating material is evenly spread on the clean surface of the magnesium alloy substrate obtained in 1.3), and then three layers of graphite paper with a thickness of 1 mm are placed on the hard coating material to obtain a premix.
[0099] 3.2) The premix obtained in 3.1) was placed in a spark plasma sintering furnace, and the process parameters of the spark plasma sintering treatment were set as follows: sintering pressure of 1t, sintering temperature of 450°C, and pressure holding time of 2min.
[0100] 3.3) After the spark plasma sintering treatment is completed, the magnesium alloy substrate is cooled to room temperature, and a hard coating is formed on the surface of the magnesium alloy substrate to obtain a coating composite material.
[0101] That is, the difference between this embodiment and embodiment 1 is only that:
[0102] In this embodiment, the volume ratio of cobalt-based tungsten carbide powder to aluminum powder is 1:1.
[0103] Example 5
[0104] This embodiment provides a surface modification method for improving the surface hardness of a magnesium alloy, comprising the following steps:
[0105] Step 1, preprocessing:
[0106] 1.1) Use an electric spark cutting machine to cut the magnesium alloy substrate to be processed into Figure 3 As shown, the magnesium alloy sample has a diameter of 40 mm and a thickness of 2 mm.
[0107] 1.2) Add an appropriate amount of clean water into the ultrasonic cleaning machine, put the cut magnesium alloy sample into the machine, turn on the ultrasonic cleaning machine, and perform cleaning for 15 minutes. After cleaning, use tweezers to take out the magnesium alloy sample and wipe it clean to obtain the magnesium alloy sample after ultrasonic cleaning.
[0108] 1.3) The composite surface of the magnesium alloy substrate after ultrasonic cleaning is polished with 400 mesh, 800 mesh and 1200 mesh fine sandpaper in sequence until the surface completely reveals the metallic luster, thereby obtaining a clean magnesium alloy substrate.
[0109] Step 2, mix cobalt-based tungsten carbide powder and aluminum powder:
[0110] According to the ratio of cobalt-based tungsten carbide powder to aluminum powder of 1:2 by volume, the corresponding mass of cobalt-based tungsten carbide powder and aluminum powder are weighed and mixed to obtain a hard coating material.
[0111] Step 3, spark plasma sintering treatment:
[0112] 3.1) Place a layer of graphite mold at the bottom. Figure 4 The graphite paper with a thickness of 1 mm is shown, and then the clean magnesium alloy substrate obtained in 1.3) is placed on the graphite paper, and then the hard coating material obtained in step 2 is coated at a temperature of 0.00348 g / mm 2 The amount of the coating material is evenly laid on the clean magnesium alloy substrate surface obtained in 1.3), and then three layers of graphite paper with a thickness of 1 mm are placed on the hard coating material to obtain a premix.
[0113] 3.2) The premix obtained in 3.1) was placed in a spark plasma sintering furnace, and the process parameters of the spark plasma sintering treatment were set as follows: sintering pressure of 1t, sintering temperature of 450°C, and pressure holding time of 2min.
[0114] 3.3) After the spark plasma sintering treatment is completed, the magnesium alloy substrate is cooled to room temperature, and a hard coating is formed on the surface of the magnesium alloy substrate to obtain a coating composite material.
[0115] That is, the difference between this embodiment and embodiment 1 is only that:
[0116] In this embodiment, the volume ratio of cobalt-based tungsten carbide powder to aluminum powder is 1:2.
[0117] Example 6
[0118] This embodiment provides a surface modification method for improving the surface hardness of a magnesium alloy, comprising the following steps:
[0119] Step 1, preprocessing:
[0120] 1.1) Use an electric spark cutting machine to cut the magnesium alloy substrate to be processed into Figure 3 As shown, the magnesium alloy sample has a diameter of 40 mm and a thickness of 2 mm.
[0121] 1.2) Add an appropriate amount of clean water into the ultrasonic cleaning machine, put the cut magnesium alloy sample into the machine, turn on the ultrasonic cleaning machine, and perform cleaning for 15 minutes. After cleaning, use tweezers to take out the magnesium alloy sample and wipe it clean to obtain the magnesium alloy sample after ultrasonic cleaning.
[0122] 1.3) The composite surface of the magnesium alloy substrate after ultrasonic cleaning is polished with 400 mesh, 800 mesh and 1200 mesh fine sandpaper in sequence until the surface completely reveals the metallic luster, thereby obtaining a clean magnesium alloy substrate.
[0123] Step 2, mix cobalt-based tungsten carbide powder and aluminum powder:
[0124] According to the volume ratio of cobalt-based tungsten carbide powder to aluminum powder of 1:4, corresponding masses of cobalt-based tungsten carbide powder and aluminum powder are weighed and mixed to obtain a hard coating material.
[0125] Step 3, spark plasma sintering treatment:
[0126] 3.1) Place a layer of graphite mold at the bottom. Figure 4 The graphite paper with a thickness of 1 mm is shown, and then the clean magnesium alloy substrate obtained in 1.3) is placed on the graphite paper, and then the hard coating material obtained in step 2 is coated at a temperature of 0.00199 g / mm 2 The amount of the coating material is evenly spread on the clean surface of the magnesium alloy substrate obtained in 1.3), and then three layers of graphite paper with a thickness of 1 mm are placed on the hard coating material to obtain a premix.
[0127] 3.2) The premix obtained in 3.1) was placed in a spark plasma sintering furnace, and the process parameters of the spark plasma sintering treatment were set as follows: sintering pressure of 1t, sintering temperature of 450°C, and pressure holding time of 2min.
[0128] 3.3) After the spark plasma sintering treatment is completed, the magnesium alloy substrate is cooled to room temperature, and a hard coating is formed on the surface of the magnesium alloy substrate to obtain a coating composite material.
[0129] That is, the difference between this embodiment and embodiment 1 is only that:
[0130] In this embodiment, the volume ratio of cobalt-based tungsten carbide powder to aluminum powder is 1:4.
[0131] Example 7
[0132] This embodiment provides a surface modification method for improving the surface hardness of a magnesium alloy, comprising the following steps:
[0133] Step 1, preprocessing:
[0134] 1.1) Use an electric spark cutting machine to cut the magnesium alloy substrate to be processed into Figure 3 As shown, the magnesium alloy sample has a diameter of 40 mm and a thickness of 2 mm.
[0135] 1.2) Add an appropriate amount of clean water into the ultrasonic cleaning machine, put the cut magnesium alloy sample into the machine, turn on the ultrasonic cleaning machine, and perform cleaning for 15 minutes. After cleaning, use tweezers to take out the magnesium alloy sample and wipe it clean to obtain the magnesium alloy sample after ultrasonic cleaning.
[0136] 1.3) The composite surface of the magnesium alloy substrate after ultrasonic cleaning is polished with 400 mesh, 800 mesh and 1200 mesh fine sandpaper in sequence until the surface completely reveals the metallic luster, thereby obtaining a clean magnesium alloy substrate.
[0137] Step 2, mix cobalt-based tungsten carbide powder and aluminum powder:
[0138] According to the ratio of cobalt-based tungsten carbide powder to aluminum powder of 1:5 by volume, the corresponding mass of cobalt-based tungsten carbide powder and aluminum powder are weighed and mixed to obtain a hard coating material.
[0139] Step 3, spark plasma sintering treatment:
[0140] 3.1) Place a layer of graphite mold at the bottom. Figure 4 The graphite paper with a thickness of 1 mm is shown, and then the clean magnesium alloy substrate obtained in 1.3) is placed on the graphite paper, and then the hard coating material obtained in step 2 is coated at a temperature of 0.00182 g / mm 2 The amount of the coating material is evenly spread on the clean surface of the magnesium alloy substrate obtained in 1.3), and then three layers of graphite paper with a thickness of 1 mm are placed on the hard coating material to obtain a premix.
[0141] 3.2) The premix obtained in 3.1) was placed in a spark plasma sintering furnace, and the process parameters of the spark plasma sintering treatment were set as follows: sintering pressure of 1t, sintering temperature of 450°C, and pressure holding time of 2min.
[0142] 3.3) After the spark plasma sintering treatment is completed, the magnesium alloy substrate is cooled to room temperature, and a hard coating is formed on the surface of the magnesium alloy substrate to obtain a coating composite material.
[0143] That is, the difference between this embodiment and embodiment 1 is only that:
[0144] In this embodiment, the volume ratio of cobalt-based tungsten carbide powder to aluminum powder is 1:5.
[0145] Example 8
[0146] This embodiment provides a surface modification method for improving the surface hardness of a magnesium alloy, comprising the following steps:
[0147] Step 1, preprocessing:
[0148] 1.1) Use an electric spark cutting machine to cut the magnesium alloy substrate to be processed into Figure 3 As shown, the magnesium alloy sample has a diameter of 40 mm and a thickness of 2 mm.
[0149] 1.2) Add an appropriate amount of clean water into the ultrasonic cleaning machine, put the cut magnesium alloy sample into the machine, turn on the ultrasonic cleaning machine, and perform cleaning for 15 minutes. After cleaning, use tweezers to take out the magnesium alloy sample and wipe it clean to obtain the magnesium alloy sample after ultrasonic cleaning.
[0150] 1.3) The composite surface of the magnesium alloy substrate after ultrasonic cleaning is polished with 400 mesh, 800 mesh and 1200 mesh fine sandpaper in sequence until the surface completely reveals the metallic luster, thereby obtaining a clean magnesium alloy substrate.
[0151] Step 2, mix cobalt-based tungsten carbide powder and aluminum powder:
[0152] According to the ratio of cobalt-based tungsten carbide powder to aluminum powder of 1:1 by volume, corresponding amounts of cobalt-based tungsten carbide powder and aluminum powder are weighed and mixed to obtain a hard coating material.
[0153] Step 3, spark plasma sintering treatment:
[0154] 3.1) Place a layer of graphite mold at the bottom. Figure 4 The graphite paper with a thickness of 1 mm is shown, and then the clean magnesium alloy substrate obtained in 1.3) is placed on the graphite paper, and then the hard coating material obtained in step 2 is coated at a temperature of 0.00348 g / mm 2 The amount of the coating material is evenly laid on the clean magnesium alloy substrate surface obtained in 1.3), and then three layers of graphite paper with a thickness of 1 mm are placed on the hard coating material to obtain a premix.
[0155] 3.2) The premix obtained in 3.1) is placed in a spark plasma sintering furnace, and the process parameters of the spark plasma sintering treatment are set as follows: sintering pressure 0.8t, sintering temperature 450°C, and holding time 2min. The process curve of this embodiment is as follows: Figure 5 shown.
[0156] 3.3) After the spark plasma sintering treatment is completed, the magnesium alloy substrate is cooled to room temperature, and a hard coating is formed on the surface of the magnesium alloy substrate to obtain a coating composite material.
[0157] That is, the difference between this embodiment and embodiment 4 is only that:
[0158] In this embodiment, the sintering pressure is 0.8t.
[0159] Comparative Example 1
[0160] This comparative example provides a surface modification method for improving the surface hardness of a magnesium alloy. The difference between this comparative example and Example 1 is only that:
[0161] In this comparative example, the volume ratio of cobalt-based tungsten carbide powder to aluminum powder is 4:1.
[0162] However, in the material finally obtained in this comparative example, the coating and the base magnesium alloy do not form an effective metallurgical bond, and the coating can be peeled off from the base magnesium alloy sheet.
[0163] Comparative Example 2
[0164] This comparative example provides a surface modification method for improving the surface hardness of a magnesium alloy. The difference between this comparative example and Example 1 is only that:
[0165] In this comparative example, no aluminum powder is contained.
[0166] However, in the material finally obtained in this comparative example, the coating and the base magnesium alloy do not form a metallurgical bond, that is, the coating is easily peeled off and cannot function as a hard layer.
[0167] Comparative Example 3
[0168] This comparative example uses the original AZ31 magnesium alloy sheet as a comparative example.
[0169] Experimental Section
[0170] (I) Effect of sintering temperature on surface hardness of magnesium alloy
[0171] In order to explore the effect of sintering temperature on the surface hardness of magnesium alloy, the present invention takes Examples 1 to 3 and Comparative Example 3 as examples, and tests and analyzes the macroscopic morphology and hardness of the coating composite materials obtained in Examples 1 to 3 and Comparative Example 3, respectively, and the results are as follows: Figure 3 , Figure 6-Figure 8 And as shown in Table 1.
[0172] Figure 3 This is a photo of the original AZ31 magnesium alloy plate of Comparative Example 3. It can be seen that the surface of the original AZ31 magnesium alloy plate is smooth and has metallic luster.
[0173] Figure 6 This is a photo of the coating composite material of Example 1. It can be seen that at 450°C and 1t pressure for 2 minutes, the black particles in the hard coating are cobalt-based tungsten carbide, and the white ones are the areas formed by sintering of aluminum powder. Figure 6 It can be seen that the hard coating in Example 1 is well bonded to the magnesium alloy, with clean edges and no peeling.
[0174] Figure 7 This is a photo of the coating composite material of Example 2. It can be seen that at 500°C and 1t pressure for 2 minutes, the black particles in the hard coating are cobalt-based tungsten carbide, and the white ones are the areas formed by the sintering of aluminum powder. Figure 7 It can be seen that the hard coating and the magnesium alloy are basically well bonded, the edge part is intact, and there is some peeling phenomenon.
[0175] Figure 8 The photo of the coating composite material of Example 3 shows that the black particles in the hard coating are cobalt-based tungsten carbide and the white particles are the sintered areas of aluminum powder at 400°C and 1t pressure for 2 minutes. Figure 8 It can be seen that the hard coating is basically well bonded to the magnesium alloy, the edges are neat and incomplete, and there is peeling in the edge area.
[0176] By comparison Figure 3 , Figure 6-Figure 8 It can be seen that when the plasma sintering temperature is 450°C, the formed hard coating material is best combined with the magnesium alloy, with complete edges and no peeling phenomenon.
[0177] Table 1 Hardness test results of the coating composite materials of Example 1 to Example 3 and Comparative Example 3
[0178] Sintering temperature / ℃ Hardness value / HV1 Example 1 450 119.4 Example 2 500 115.64 Example 3 400 108.56 Comparative Example 3 - 77.76
[0179] Table 1 shows the hardness test results of the coating composite materials of Examples 1 to 3 and Comparative Example 3. According to the test results in Table 1, it can be seen that the hardness of the coating composite materials prepared in Examples 1 to 3 of the present invention is significantly improved compared with the original AZ31 magnesium alloy sheet, which indicates that the preparation method of the present invention can effectively improve the hardness of the magnesium alloy surface.
[0180] By comparing the test results of Example 1 to Example 3, it can be seen that when the sintering temperature is 450° C., the hardness value of the prepared coating composite material is the highest, which is 119.4 HV1.
[0181] In summary, when the sintering temperature is 450°C, in the prepared coating composite material, the hard coating is well bonded to the magnesium alloy, the edges are neat, there is no peeling phenomenon, and the hardness value is the highest. Therefore, the present invention further prefers that the sintering temperature is 450°C.
[0182] (II) Effect of the mixing ratio of cobalt-based tungsten carbide powder and aluminum powder on the surface hardness of magnesium alloy
[0183] Based on the above research results, in order to explore the effect of the mixing ratio of cobalt-based tungsten carbide powder and aluminum powder on the surface hardness of magnesium alloy, the present invention takes Example 1, Example 4-Example 7 and Comparative Example 1-Comparative Example 3 as examples, and tests and analyzes the macroscopic morphology and hardness of the obtained coating composite materials, and the results are as follows: Figure 6 , Figure 9-Figure 14 And as shown in Table 2.
[0184] Figure 6 This is a photo of the coating composite material of Example 1. It can be seen that the black particles in the hard coating on the surface of Example 1 are cobalt-based tungsten carbide, and the white ones are areas formed by sintering of aluminum powder. It can also be seen that the hard coating on the surface of Example 1 is well combined with the magnesium alloy, with neat edges and no peeling.
[0185] Fig. 9 This is a photo of the coating composite material of Example 4. It can be seen that the hard coating of Example 4 is basically black, the black is the color of cobalt-based tungsten carbide, and the white part is the area formed by sintering of aluminum powder. It can also be seen that the hard coating is well combined with the magnesium alloy, the edges are neat, and there is no obvious peeling phenomenon.
[0186] Fig.10 This is a photo of the coating composite material of Example 5. It can be seen that in the hard coating of Example 5, the black color is the color of cobalt-based tungsten carbide, and the white color is the area formed by sintering of aluminum powder. It can also be seen that the hard coating is well combined with the magnesium alloy, the edges are basically neat, and there is peeling in some areas of the edge of the sample.
[0187] Fig.11 This is a photo of the coating composite material of Example 6. It can be seen that the black color in the hard coating of Example 6 is the color of cobalt-based tungsten carbide, and the white color is the area formed by sintering of aluminum powder. It can also be seen that the hard coating is well combined with the magnesium alloy, and the edge of the sample is basically intact without obvious peeling.
[0188] Fig.12 This is a photo of the coating composite material of Example 7. It can be seen that the hard coating of Example 7 is basically black, the black is the color of cobalt-based tungsten carbide, and the white part is the aluminum powder after melting. It can also be seen that the hard coating is basically well combined with the magnesium alloy, and there is obvious peeling at the edge.
[0189] Fig.13 This is a photo of the coating composite material of Comparative Example 1. It can be seen that when the volume ratio of cobalt-based tungsten carbide to aluminum powder is 4:1, the surface of the sample coating is black, the hard coating is not well bonded to the magnesium alloy, there is obvious peeling at the edge, and the coating is cracked when the hardness is tested.
[0190] Fig.14 This is a photo of the coating composite material of Comparative Example 2. It can be seen that when the hard coating is pure cobalt-based tungsten carbide, the surface of the sample coating is black, the coating is not well bonded to the magnesium alloy, there are obvious cracks in the middle of the coating, and there is obvious peeling phenomenon as a whole, and the hardness of the coating itself cannot be measured.
[0191] By comparison Figure 6 and Figure 9-Figure 14 It can be seen that when the volume ratio of cobalt-based tungsten carbide powder to aluminum powder is 1:1-4, a complete hard coating can be obtained under the process conditions of 450°C and 1t pressure for 2 minutes. However, when the volume ratio of cobalt-based tungsten carbide powder to aluminum powder is greater than 1, the hard coating will peel off, that is, the hard coating and the matrix magnesium alloy cannot achieve a good organic combination.
[0192] Table 2 Hardness test results of the coating composite materials of Example 1, Example 4-Example 7 and Comparative Example 1-Comparative Example 3
[0193] Volume ratio of cobalt-based tungsten carbide powder and aluminum powder Hardness value / HV1 Example 1 1:3 119.4 Example 4 1:1 120.93 Example 5 1:2 116.85 Example 6 1:4 111.01 Example 7 1:5 96.69 Comparative Example 1 4:1 - Comparative Example 2 Pure Cobalt-based Tungsten Carbide Powder - Comparative Example 3 Hardness of original magnesium alloy sheet 77.76
[0194] Table 2 shows the hardness test results of the coating composite materials of Example 1, Examples 4 to 7 and Comparative Examples 1 to 3.
[0195] According to the test results in Table 2, it can be seen that the hardness of Example 1 is 119.4HV1, the hardness of Example 4 is 120.93HV1, the hardness of Example 5 is 116.85HV1, the hardness of Example 6 is 111.01HV1, the hardness of Example 7 is 96.69HV1, and the hardness of Comparative Example 3 is 77.76HV1, which shows that the hardness of the coating composite materials prepared by Example 1, Example 4-Example 7 of the present invention is significantly improved relative to the original AZ31 magnesium alloy sheet, which shows that the preparation method of the present invention can effectively improve the hardness of the magnesium alloy surface. Among them, since the volume ratio of the content of cobalt-based tungsten carbide powder to aluminum powder in Comparative Example 1 is greater than 1:1, the quality of the combination of the mixed body and the substrate in the hard coating material is poor, and no effective metallurgical bonding is formed. The coating is broken when the hardness is measured, and the hardness value cannot be tested. In Comparative Example 2, since no aluminum powder is added, the cobalt-based tungsten carbide cannot be compounded on the magnesium alloy substrate, and there is no hardness value.
[0196] By comparing the test results of Example 1, Example 4-Example 7 and Comparative Example 1-Comparative Example 2, it can be seen that when no aluminum powder is added, or the amount of aluminum powder added is less than 1:1, a hard coating cannot be formed on the surface of the magnesium alloy, and it is difficult to improve the hardness of the surface of the magnesium alloy. This verifies that the present invention is to add aluminum powder, melt the aluminum powder and mechanically mix it with the cobalt-based tungsten carbide powder, and then form a hard coating on the surface of the magnesium alloy, thereby improving the hardness of the surface of the magnesium alloy. It can also be seen that when the amount of aluminum powder added is too much, the effect of improving the hardness of the surface of the magnesium alloy will decrease. Therefore, the preferred volume ratio of the cobalt-based tungsten carbide powder to the aluminum powder is 1:1 to 5. More preferably, it is 1:1 to 3.
[0197] (III) Effect of sintering pressure on surface hardness of magnesium alloy
[0198] Based on the above research results, in order to explore the effect of sintering pressure on the surface hardness of magnesium alloy, the present invention takes Example 4 and Example 8 as examples to test and analyze the hardness of the obtained coating composite materials, and the results are shown in Table 3.
[0199] Table 3 Hardness test results of the coating composite materials of Example 1 and Example 8
[0200] Sintering pressure / t Hardness value / HV1 Example 4 1 120.93 Example 8 0.8 112.36
[0201] According to the test results in Table 3, the preparation method of the present invention can improve the hardness of the material at 0.8t to 1t while minimizing the deformation of the material, which is beneficial to the practical application of subsequent related enterprises.
[0202] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A surface modification method for improving the surface hardness of a magnesium alloy, characterized in that: The following steps are involved: Pre-treating the magnesium alloy substrate to be treated to remove surface impurities and oxide layers to obtain a clean magnesium alloy substrate; The cobalt-based tungsten carbide powder and the aluminum powder are mixed to obtain a hard coating material; The hard coating material is evenly spread on the surface of the clean magnesium alloy substrate to obtain a premix; the premix is subjected to spark plasma sintering treatment so that the hard coating material forms a hard coating metallurgically bonded to the magnesium alloy substrate on the surface of the magnesium alloy substrate to improve the surface hardness of the magnesium alloy substrate.
2. The surface modification method according to claim 1, characterized in that: The volume ratio of the cobalt-based tungsten carbide powder to the aluminum powder is 1:1-5.
3. The surface modification method according to claim 1, characterized in that: The sintering pressure of the spark plasma sintering treatment is 0.8t-1t, and the sintering temperature is 400°C-500°C.
4. The surface modification method according to claim 1, characterized in that: The holding time of the spark plasma sintering treatment is 1 min to 3 min.
5. The surface modification method according to claim 1, characterized in that: The amount of the hard coating material laid on the surface of the clean magnesium alloy substrate is 0.00187 g / mm 2 ~0.00597g / mm 2 .
6. The surface modification method according to claim 1, characterized in that: The average particle size of the cobalt-based tungsten carbide powder is 10 μm to 30 μm.
7. The surface modification method according to claim 1, characterized in that: The average particle size of the aluminum powder is 10 μm to 20 μm.
8. The surface modification method according to claim 1, characterized in that: The pretreatment includes ultrasonic cleaning and polishing.
9. The surface modification method according to claim 8, characterized in that: The cleaning liquid for the ultrasonic cleaning treatment is water, and the ultrasonic time is 10 minutes to 20 minutes.
10. The surface modification method according to claim 8, characterized in that: The polishing process is carried out by the following steps: The magnesium alloy composite surface after ultrasonic cleaning was polished with 400-mesh, 800-mesh and 1200-mesh fine sandpaper in sequence until the surface completely exposed the metallic luster.